Effect of Tax Payment on Performance of Small-Scale Businesses in Uganda: A Case Study of Bwambara Sub-County Rukungiri District. - Akampurira, Space (Kabale University, 2024)
The study was about the effect of taxes on the performance of small-scale business enterprises in Uganda; A case study of Bwambara Trading Centre in Rukungiri district. A descriptive design and exploratory design were used depending on the characteristics of the study. A sample of 88 respondents was used, and data was collected using a questionnaire directed to the owners of small-scale enterprises in the area. Data was analyzed and summarised using frequencies where percentages were derived for easy interpretation. The findings of the study revealed that taxations promote funding of governments; it also affects the savings and investments of business operators. The study also revealed that taxation also causes some business people to lose jobs, and also makes increments in prices for goods and services in SMEs. The study recommends that the Government through the Ministry of Finance Planning and Economic Development call for workshops, seminars, and radio programs to educate the business community about the different forms of taxes imposed on small-scale businesses. The study revealed that the biggest problem with the tax paid is in fact that the SME community does not understand how the tax is arrived at as well as how it is paid but not because it is too high.